Development of Game-Based Mathematics Learning Media to Improve Mathematical Understanding Abilities - Sita Rahmawati; Muhammad Jamaluddin (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2024)
This research aims to develop mathematics learning media in the form of games. Apart from that, this research aims to determine the feasibility and find out whether the learning media being developed is appropriate and can improve students' understanding abilities in mathematics subjects. This type of research is development research with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects were class VII students at YP Sunan Dalem Gumeno Middle School. The research instruments used in this research were (1) Interview Guide (2) Validation Sheet (3) Student Response Questionnaire (4) Mathematical Understanding Ability Test Questions. The mathematics learning media in the form of games developed is expected to improve students' mathematical understanding abilities. The validation results from media experts and material experts respectively obtained an average of 4.4 and 4.2 with valid criteria. The validation results of the mathematical understanding ability test obtained an average score of 4.2 with valid criteria. The results of the student response questionnaire obtained an average practicality of 4.2 with practical criteria. The results of the mathematical understanding ability test were carried out using a t-test using the SPSS program and the results showed that the significant value was 0.000 < 0.05, meaning that students' mathematical understanding ability after using game learning media was better before using the game learning media, so it can be concluded that the learning media Games can improve students' mathematical understanding abilities and can be said to be effective. The results of this research show that learning media is said to be valid, practical, and effective. In other words, game-based mathematics learning media can improve students' mathematical understanding abilities.